Distinctive features of eye pathology in elderly and senile people in Arkhangelsk region - R. N. Zelentsov; V. V. Popov; I. A. Novikova; A. A. Trofimova (Российский офтальмологический журнал)
Purpose: to identify the features of the pathology of the eye in elderly and senile people in the Arkhangelsk region.   Material and methods. Annual reports of medical eye care facilities for the 2009 to 2019 who offered ophthalmological assistance to individuals aged 60 or older were analyzed. To estimate the differences infrequency of occurrence Pearson's Chi-square was used.   Results. The incidence of eye pathologies in elderly and senile people amounts to 20.74% (17.83 % male and 22.29 % female). The most common conditions included the pathology of the lens that occurred in almost 50 % of the old people, glaucoma was diagnosed in about 20 % and retinal conditions in one out of seven people. In the age group of 60 to 74 years, the most common pathologies included glaucoma, diabetic angioretinopathy, retinal conditions and refractive errors; in the people of advanced age (75—89 years), lens pathologies and age-related macular degeneration occurred more frequently than in the younger age group while glaucoma, diabetic angioretinopathy, retinal conditions and refractive errors occurred less frequently. The oldest age group (90 years and older) showed a different pathology distribution than people of the younger age groups: they have higher occurrence of lens pathologies, age-related macular degeneration, optic disc pathology. In contrast, they have a rarer occurrence of retinal diseases, whilst diabetic angioretinopathy or refractive errors were not diagnosed at all. Gender differences of eye pathology distribution are revealed in the fact that, among people aged 60 to 89, women have a higher occurrence of age-related macular degeneration, retinal diseases and refractive errors, while men are more often diagnosed with glaucoma.   Conclusion. The identified features of eye pathology in elderly and senile people living in the Arkhangelsk region should be taken into account when medical care for advanced age groups is developed and improved.